Langley Calibration Analysis of Solar Spectroradiometric Measurements: Spectral Aerosol Optical Thickness Retrievals. Issue 8 (21st April 2018) - Jeong, Ukkyo; Tsay, Si‐Chee; Pantina, Peter; Butler, James J.; Loftus, Adrian M.; Abuhassan, Nader; Herman, Jay R.; Dimov, Alexander; Holben, Brent N.; Swap, Robert J.
Abstract: Aerosol optical thickness ( τ aer ) is a fundamental parameter for analyzing aerosol loading and associated radiative effects. The τ aer can constrain many inversion algorithms using passive/active sensor measurements to retrieve other aerosol properties and/or the abundance of trace gases. In the next wave of spectroradiometric observations from geostationary platforms, we envision that a strategically distributed network of robust, well‐calibrated ground‐based spectroradiometers will comprehensively complement spaceborne measurements in spectral and temporal domains. Spectral τ aer can be accurately obtained from direct‐Sun measurements based on the Langley calibration method, which allows for the analysis of distinct spectral features of the calibration results. In this study, we present a spectral τ aer retrieval algorithm for an in‐house developed, field deployable spectroradiometer instrument covering wavelengths from ultraviolet to near‐infrared (UV‐Vis‐NIR). The spectral total optical thickness obtained from the Langley calibration method is partitioned into molecular and particulate components by utilizing a least squares method. The resulting high temporal‐resolution τ aer and Ångström Exponent can be used effectively for cloud screening. The new algorithm was applied to month‐long measurements acquired from the rooftop at National Aeronautics and Space Administration Goddard Space Flight Center's Building 33. The retrieved τ aer demonstrated excellent agreement with those from well‐calibrated Aerosol Robotic Network Sun photometers at all overlapping wavelengths (correlation coefficients higher than 0.98). In addition, empirical stray light corrections considerably improved τ aer retrievals at short wavelengths in the UV. The continuous spectrum of τ aer from UV‐Vis‐NIR spectroradiometers is expected to provide more informative constraints for retrieval of additional aerosol properties such as refractive indices, size, and bulk vertical distribution. Key Points: Spectral aerosol optical thickness retrieval algorithm was developed based on the Langley calibration method Developed empirical stray light correction method considerably improved aerosol optical thickness retrievals at ultraviolet wavelengths Retrieved spectral aerosol optical thickness provides the key constraints for additional aerosol properties and trace gas retrievals